Features and Problems of Inventory Accounting in Current Assets of Construction Organizations based on the Supply Chain Strategies - Elena Sergeevna, Sergushina; Oleg Vladimirovich, Kabanov; Julia Evgenievna, Starostina; Alexander, Yakovlev; Klykov, Michael; Ekaterina Yurevna, Kamchatova; Bestaeva, Liya; Evgeny Konstantinovich, Osipov (ExcelingTech, 2020)
Abstract The future looks bright for the infrastructure sector and we have made incredibly positive steps towards evolving our practices to collaborate with supply chain partners. Sustainability in the supply chain is becoming more and more important for industrialenterprises in different sectors. This research article focuses on construction supply chains in the industry, where every product is almost unique based on specificcustomer needs and requirements. The article deals with the essence and concept of current assets of an enterprise and their management in the field of construction activities. The concept of material and production stocks, their features and problems of accounting in a construction organization are specified.